STUDI TENTANG ISLAMIC SOCIAL REPORTING PADA BANK SYARIAH: PERAN UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE - Fahitaratih, Syafira Maistin; Tubastuvi, Naelati; Purwidianti, Wida; Aryoko, Yudhistira Pradhipta (COMPETITIVE, 2024)
The Islamic Social Reporting Index measures the extent to which companies comply with Sharia principles in their annual reports, assessing the level of social transparency. These factors are company size, profitability, and leverage, advertising in this research is to assess its impact on Islamic Social Reporting. This research focuses on the population of Sharia Commercial Banks in Indonesia for the 2017-2022 period, specifically examining their annual reports. The sample size for this research is 15 Sharia Commercial Banks in Indonesia. with a total of 66 data. This research uses quantitative methodology. Islamic Social Reporting (ISR) uses the ISR index as a measuring tool applied in the annual reports of Islamic banking institutions. This research uses various data analysis methodologies, namely Descriptive Statistical Analysis, Classical Assumption Test, and Linear Regression Test using the SPSS application. The findings of this research show that there is a positive influence between company size and Islamic Social Reporting, while there is a negative impact between profitability and Islamic Social Reporting. Islamic Social Reporting remains unaffected by factors such as leverage.